Entrepreneurship Information Awareness among Undergraduates in Adeyemi College of Education, Ondo - Akerele, Johnson Ayodeji (MiddleBelt Journal of Library and Information Science, 2020)
One of the major problems facing the Nigerian youths is unemployment. This challenge can be addressed if adequate attention is paid to creating awareness in respect of entrepreneurship information among them. Consequently, this study investigated entrepreneurship information awareness among 300 level degree students of the Department of Economics, Adeyemi College of Education, Ondo, Ondo State. Total enumeration sampling technique was used to distribute questionnaire to all the 126 degree III students of the Department Economics, Adeyemi College of Education, Ondo. The research instrument used in this study was a self-developed 4-section questionnaire, titled: Undergraduates Entrepreneurship Information Awareness Questionnaire, UEIAQ. Out of the 126 questionnaire distributed, only 94 were returned and found useful. Therefore the study’s response rate was 74.60%. The study found that 75.53% of the respondents were able to correctly defined entrepreneurship, 70.21% stated that they disliked entrepreneurship but prefer white collar jobs and many of the undergraduates have low level of entrepreneurship information awareness. It was recommended that librarians should create more awareness on the importance of entrepreneurship information and its relevance to the National economic development. Finally, government should build an entrepreneur-friendly environment through provisions of amenities such as stabled power supply, prompt access to capital and good roads.